Evaluation of internal corrosion in a Brazilian iron ore slurry pipeline based on the characterization of scales and tubercles - Mattioli,Gabriela Goes (2018)
Abstract The transport capacity of long-distance slurry pumping systems is directly related to the roughness of the pipe. In this context, corrosion plays an important role, especially when dealing with old pipes. Chemical, mineralogical and microstructural analyses were performed on materials removed from the internal surface of an iron ore slurry pipeline in order to access their composition and to check if they were a result of internal pipeline corrosion. This pipeline has been operating since 1977. It was found that the tubercles formed on the internal wall of the pipe presented botryoidal magnetite as their essential composition. As the amount of magnetite is very low in the transported slurry and magnetite with botryoidal morphology is not present in the processed iron ore, it was concluded that this magnetite is a result of a corrosion process occurring on the internal wall of the pipeline.